POLEMIK AMALAN KHITĀN WANITA DI MALAYSIA MENURUT PERSPEKTIF ISLAM: SUATU KAJIAN AWAL: Polemics Surrounding Female Circumcision Practices in Malaysia from an Islamic Perspective: A Review - Mohd Ithnin, Norazam Khair; Suliaman, Ishak; Ibrahim, Abdul Halim (Jurnal Fiqh, 2023)
The practice of female circumcision in Malaysia has been heavily criticized as being similar to Female Genital Mutilation (FGM) in Africa. This criticism followed a 2018 United Nations Human Rights (UNHR) Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) recommendation, which called on Malaysia to stop the practice. Among the claims made were that female circumcision is just a tradition and not a religious requirement, and that the hadith used to justify the practice is not authoritative. This study aims to identify the polemics surrounding the practice of female circumcision in Malaysia. It is an initial qualitative study that uses content analysis to analyze data. The study found that there are five main reasons that have caused the polemics regarding female circumcision in Malaysia such as a disagreement regarding the practice of female circumcision in Malaysia, with some viewing it as a local custom. Furthermore, contemporary scholars are debating its legitimacy based on the authentication of relevant hadith sources. Meanwhile, the different methods employed raise concerns about the understanding and implementation of female circumcision among medical practitioners in Malaysia, further exacerbated by the absence of authoritative guidelines on female circumcision by regulatory authorities in Malaysia. In conclusion, this study suggests that the polemics surrounding female circumcision in Malaysia must be resolved by continuing research that can produce safe and Shariah-compliant guidelines.